Gospodarka regionów granicznych w procesie integracji europejskiej - Dorocki, Sławomir (Przedsiębiorczość - Edukacja, 2010)
The aim of the article is an analysis of regional diversity in economic activity in European society.The following work presents the issue of the effectiveness of European regional politics,namely the process of equation of economic development level in reference to present-dayinternational borders. Both territorial diversity and the changes in the dimensions of chosenratios were analyzed. The analysis covered the statistical regions of second level EuropeanUnion member states. Interest in the diversity of border regions influenced the choice of thosestates which do not border with other regions. The focus on member states from western Europewas a result of the delay in the analysis of regional policies of recently joined EuropeanUnion member states and the consequent lack of comparable statistical data. The analysisincludes regions belonging to: Austria, Belgium, Denmark, France, Finland, Greece, Spain,Holland, Germany, Portugal and Sweden and relates to the years: 2006-2007. The analysisdiscusses the dimension of investment in relation to the number of employed, growth rate ofthe employed and the number of economic subjects in reference to the number of employed.